Market intergration and currency risk pricing in chinese mainland and equity market: evidence from Shanghai-Hong Kong stock connect - Lei, Wei (My University, 2018)
This paper investigates the two topics of market integration and currency risk pricing in the Chinese mainland equity market. It also examines the impact of liberalization policies, including currency reform and Shanghai-Hong Kong Stock Connect on the two topics. This paper employs both an unconditional multi-beta pricing model under the International Arbitrage Pricing Theory framework, and a conditional pricing model using the multivariate GARCH-in-Mean setup. Using both monthly data and weekly data covering the period through January 2001 to September 2017, I find both world market risk and Chinese local market risk are positively priced in the Chinese mainland equity market, providing evidence of partial integration. A weak upward trend is detected for the low correlation between the Chinese mainland equity market and the world market. Currency risk is found to be negatively priced with a time-varying price. While world market risk and currency risk constitute essential components of the long-run total risk premium in the Chinese mainland equity market, local risks remain the dominant source in determining the short-run variations in the total risk premium. A structural shift in risk pricing is detected after the currency reform for both world market risk and currency risk, making the positive price of world market risk more positive and the negative price of currency risk even more negative. Although foreign participation has increased rapidly after Shanghai-Hong Kong Stock Connect, there are no significant changes observed in the pricing process. These findings suggest that international investors can still enjoy diversification benefit from the Chinese mainland equity market because of the low level of correlation and partial integration, but they must pay enough attention to the local source of risks and currency risk, and follow closely further liberalization policies.
A research paper submitted in partial fulfilment of the requirement for the for Degree of Master of Management in Finance and Investment Graduate School of Business Administration University of the Witwatersrand May 28, 2018
Keywords: Stock options; Investment analysis--South Africa; China--Economic conditions